Narcissism In Baroness The Antagonist In Cruella Movie (2021): Heinz Kohut’s Perspective - Febriyani, Anggita Vina; Sumayah (International Journal of English Linguistics, Literature, and Education (IJELLE), 2024)
This study analyzes the narcissistic traits of Baroness, the antagonist in Cruella (2021), using Heinz Kohut's self-psychology theory. The research aims to (1) identify indicators of narcissism based on Kohut's perspective and (2) examine how Baroness's actions represent narcissistic characteristics. A qualitative method was applied to analyze 23 instances of Baroness's behavior, dialogue, and monologue, categorized into five narcissistic traits: grandiose self (39%), lack of empathy (26%), exploitativeness (17%), need for admiration (9%), and narcissistic rage (9%). Data were collected from the film and supported by psychoanalytic theories, e-journals, and literature on narcissism, with analysis conducted using Miles and Huberman's interactive model. The findings reveal Baroness’s grandiose self through her superiority complex and relentless desire for recognition. Her lack of empathy and exploitativeness are evident in her manipulation and disregard for others, while her need for admiration and narcissistic rage highlight her fragile self-esteem and defensive reactions when her authority is challenged. These traits align with Kohut's theory, emphasizing how unmet early emotional needs can lead to pathological narcissism. The study underscores the film's capacity to portray psychological and social issues, providing insights into mental health representations in popular culture and encouraging further exploration of their societal implications.